(untitled) (Asian Journal of Medical and Biological Research, 2025)
Guava (Psidium guajava L.) is a highly perishable tropical fruit that undergoes rapid postharvest deterioration, leading to significant losses in quality and market value. This study aimed to evaluate the effectiveness of natural plant extracts—ginger (Zingiber officinale), moringa (Moringa oleifera), and garlic (Allium sativum)—in maintaining the postharvest quality and extending the shelf life of guava fruits. Freshly harvested guavas were treated with aqueous extracts of these plants, while untreated fruits served as controls. All fruits were stored under ambient conditions for eight days, and changes in weight loss, firmness, total soluble solids (TSS), titratable acidity (TA), pH, vitamin C content, moisture, dry matter, and overall shelf life were analyzed using inferential statistical methods. Results showed that all fruits experienced a gradual loss of weight and firmness, but the extent varied among treatments. Ginger-treated fruits exhibited the least weight loss and highest firmness retention, followed by moringa and garlic, while control fruits deteriorated most rapidly. TSS increased over time in all samples, whereas TA and vitamin C declined, with ginger-treated fruits retaining higher acidity and vitamin C levels. A slight increase in pH and dry matter, and a corresponding decrease in moisture, were observed across all treatments. The estimated shelf life was longest in ginger-treated fruits (11.67 days), followed by moringa (10.67 days), garlic (8.67 days), and control (7.67 days). These findings indicate that ginger and moringa extracts can slow ripening, maintain nutritional quality, and provide practical, eco-friendly options for improving guava storage, reducing postharvest losses, and enhancing market value. The study provides practical guidance for farmers and the fruit industry to use ginger and moringa extracts as natural, cost-effective methods to enhance guava shelf life and marketability. Asian J. Med. Biol. Res. 2025, 11(4), 104-113